SAD in the summer : symptoms in summer- vs. winter subtype of seasonality - Ásta Guðrún Birgisdóttir 1980- (2022)
Seasonal affective disorder (SAD), and even more so a sad mood in winter, are common in northern countries with long and dark winters. However, in hot countries summer depression is more common, when the days are long and hot, and it is burdensome to stay inside. In northern countries the long days, albeit not being hot, are a burden for some people. However, the difference between people with more sensitivity in mood to summer, compared to a similar condition in winter, is under researched in the northern countries, and no such study has been found which examines this phenomenon in Iceland. The main goal of this thesis is to study the difference between symptoms of individuals with low mood in summer compared to individuals with low mood in winter. Furthermore, we will gain an idea of how many people in Iceland experience negative low mood in summer compared to winter. The study is based on an online survey with around 350 participants that were recruited in summer 2021 which were followed up every three months, for a total of three occasions. A total of 209 participants were found to feel worst in the summer and in the winter. Comparative statistics with the Mann-Whitney-U tests were examined to study differences between groups of people and seasons. There was no significant difference between depressive symptoms and quality of sleep between people feeling worst in the summer as compared to winter. There was a difference between male participants when asked about the questions “I felt that life was meaningless” and “I felt that I had nothing to look forward to” in DASS-21 as compared to female participants, which was not significant after correction for multiple comparisons. No significant difference was found between genders on specific depressive symptoms or overall depression scores, neither in summer, nor in winter. Further research on summer depression and feeling worst in the summer is needed, especially due to global climate change. The effect on people's well-being needs to be examined, as high ...